Upaya India Dalam Meningkatkan Pariwisata Pasca Mumbai Attack Tahun 2008 - Ningrat, Komang Ayu Rahajeng; Priardarsini, Ni Wayan Rainy; Parameswari, A.A Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The Mumbai Attack 2008 was one of terrorism attack that seized so much attention of the international community. After the incident, India's national security was in the spotlight and had a major impact on India's tourism and economy. It was marked by the issuance of travel advisory status by several countries and a number of withdrawals of foreign investment in India. This study discusses India's efforts to increase tourism after the 2008 Mumbai attack by using tourism in international relation and safety & tourism as the concept. The discussion will be divided into two efforts: security efforts and tourism efforts, which are two interrelated things.   Keywords: mumbai attack, terrorism, tourism, security .